Intake of Animal-Based Foods and Consumer Behaviour towards Organic Food: The Case of Nepal - Mausam Budhathoki (MDPI AG, 2021)
This study aims to segment Nepalese consumers based on the frequency of animal-based food intake and thereby the determinants of organic food purchasing behaviour to suggest possible marketing strategies for organic food suppliers. A face-to-face survey was conducted among Nepalese consumers (n = 527), underpinned by the theoretical framework, ‘theory of planned behaviour (TPB)’, and extended to include: knowledge, environmental concerns, health-consciousness, and background factors (socio-demographic and lifestyle characteristics). Three segments of consumer types were identified by employing k-means segmentation: All Low (n = 113), High Dairy (n = 246), and High Dairy and Meat (n = 168). A covariance-based structural equation modelling (CB-SEM) analysis indicated that perceived behavioural control (β = 0.438, p < 0.001) was the main predictor of organic food purchasing intention, followed by attitude (β = 0.302, p < 0.001), subjective norms (β = 0.300, p < 0.001), knowledge (β = 0.211, p < 0.001), and environmental concerns (β = 0.208, p < 0.001). Health-consciousness (β = −0.034, p = 0.374) showed no significant impact on organic food purchasing intention. Organic food purchasing intention had a strong positive impact on organic food purchasing behaviour. Socio-demographic and lifestyle characteristics were found to impact behavioural intention indirectly by their effects on attitude, subjective norms, perceived behavioural control, knowledge, and environmental concern. Income also had a direct impact on organic food purchasing behaviour. Further, consumers with a low intake of animal-based foods held positive attitudes towards organic food and had higher environmental concerns. The findings can be used to inform organic food producers and targeted marketing campaigns towards promoting organic food purchasing behaviour in Nepal and similar countries.